Chronic kidney disease progression in kidney transplant recipients: A focus on traditional risk factors. Issue 2 (29th January 2019) - Carminatti, Moisés; Tedesco‐Silva, Hélio; Silva Fernandes, Natália Maria; Sanders‐Pinheiro, Helady
ABSTRACT: Kidney transplant recipients are a subset of patients with chronic kidney disease (CKD) that remain at high risk for progression to dialysis and mortality. Recent advances in immunosuppression have only partially improved long‐term graft and patient survival. Discovery of new immunosuppressive regimens is a slow and resource‐intensive process. Hence, recognition and management of modifiable allogeneic and non‐allogeneic risk factors for progression to CKD among kidney transplant recipients is of major interest for improving long‐term outcomes. Graft survival is mainly determined by the quality of the allograft and by the patient's alloimmune response, which is influenced by human leukocyte antigen matching and the presence of donor‐specific antibodies. Alloimmune responses manifest as acute and chronic forms of cell‐ and antibody‐mediated rejection, which can be worsened by patient non‐adherence or under‐immunosuppression. However, donor and patient ages, glomerular disease recurrence, time on dialysis, pre‐existing cardiovascular burden, medication side‐effects and traditional risk factors, such as hypertension, proteinuria, anaemia, dyslipidaemia, diabetes and bone mineral disorder, which can ultimately lead to severe endothelial derangement, also contribute to graft loss and mortality. These traditional risk factors, common to pre‐dialysis patients, often are considered of secondary importance when compared to alloimmunity and immunosuppression concerns. In this review article, we focus on the epidemiological, pathophysiological and therapeutic features of non‐allogeneic traditional risk factors for CKD. We also discuss the benefit of adopting a multidisciplinary approach to pursue the same therapeutic targets recommended for pre‐dialysis patients. Summary at a Glance: This is a narrative review of the intervention and recommended treatment targets of non‐allogeneic risk factors in reducing chronic kidney disease progression and mortality in kidney transplant recipients. The importance of a multidisciplinary approach to target these risk factors is emphasised. The authors have also provided a summary of the clinical targets/practical approach in the treatment of these risk factors.